Steganography With Improved Cryptography - Gyarsia, Yogesh; Tiwari, Shiv (International Journal of Computer Sciences and Engineering, 2025)
With the development of technology, secret communication with audio, image and video files has become important. In this case, encryption and steganography play a major role. While encryption deals with uncatchable of message content, steganography deals with failure to understand the existence of the messages used for secret communication. Because of these features steganography and encryption are the two main elements complementing each other. The steganography is the art of hidden; its main aim is to pass unnoticed data in another data. There are many types of data that used in steganography, such as message, image, and video. In this work, we are interested in hiding a message inside an image and also securing it. Our work focuses on the study of least significant bit (LSB) technique for embedding text into image. Moreover, we propose an improved approach for LSB based image steganography and encryption decryption using partitioning, zigzag and swapping.